Spindle pole body component 25 and platelet-derived growth factor mediate crosstalk between tumor-associated macrophages and prostate cancer cells - Cui, Feilun; Xu, Zhipeng; Hu, Jianpeng; Lv, Yumei (Frontiers in Immunology, 2022)
Tumor-associated macrophages (TAMs) are involved in the growth of prostate cancer (PrC), while the molecular mechanisms underlying the interactive crosstalk between TAM and PrC cells remain largely unknown. Platelet-derived growth factor (PDGF) is known to promote mesenchymal stromal cell chemotaxis to the tumor microenvironment. Recently, activation of spindle pole body component 25 (SPC25) has been shown to promote PrC cell proliferation and is associated with PrC stemness. Here, the relationship between SPC25 and PDGF in the crosstalk between TAM and PrC was investigated. Significant increases in both PDGF and SPC25 levels were detected in PrC specimens compared to paired adjacent normal prostate tissues. A significant correlation was detected between PDGF and SPC25 levels in PrC specimens and cell lines. SPC25 increased PDGF production and tumor cell growth in cultured PrC cells and in xenotransplantation. Mechanistically, SPC25 appeared to activate PDGF in PrC likely through Early Growth Response 1 (Egr1), while the secreted PDGF signaled to TAM through PDGFR on macrophages and polarized macrophages, which, in turn, induced the growth of PrC cells likely through their production and secretion of transforming growth factor β1 (TGFβ1). Thus, our data suggest that SPC25 triggers the crosstalk between TAM and PrC cells via SPC25/PDGF/PDGFR/TGFβ1 receptor signaling to enhance PrC growth.